HUBUNGAN KOMUNIKASI INTERPERSONAL DALAM KELUARGA DENGAN KECERDASAN EMOSIONAL SISWA SERTA IMPLIKASINYA DALAM PELAYANAN BIMBINGAN DAN KONSELING - Rizki, Tanzilal Wanda; Mudjiran, Mudjiran (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Emotional Intelligence is the ability to motivate yourself, resolve the frustration, control the pressure, adjust mood, empathy and the ability to work in team. In fact, we found that there are still students who speak harshly to their friends, often cursing others and even there are students who easily get angry and tempered when their friends give a joke. One of the factors that influence it is interpersonal communication in their family. The purpose of this study is to: (1) describe students’  emotional intelligence, (2) describe interpersonal communication in their family, and (3) test the significance of the relationship of the interpersonal communication in the family with students emotional intelligence.  This research is a quantitative research with descriptive correlational type. The population of this study were 475 students of SMA Adabiah 2 Padang  and a sample in number of 219 students that is selected by Stratified Random Sampling method. The instruments which used were interpersonal communication  in students family and students' emotional intelligence questionnaires. Data were analyzed by descriptive statistical techniques and Pearson Product Moment techniques. This research found  that: (1) the interpersonal communication in family was in a good category with its percentage is 77.54%, (2) students' emotional intelligence in the high category with its percentage is 77.48%, (3) there is a significant positive relationship between interpersonal communication in the family and students' emotional intelligence with a correlation coefficient is 0.578 and a significance level is 0.000. It can be concluded that there is a significantly positive relationship between interpersonal communication in family and students' emotional intelligence.Keywords: Interpersonal Communication, Family, Emotional Intelligence.